Applications of Mathematics and Statistics in Economics 2017
DOI: 10.15611/amse.2017.20.31
|View full text |Cite
|
Sign up to set email alerts
|

Selected Gender Gap Indicators – Comparison of V4 Countries within EU Context

Abstract: The paper examines similarities and distinctions of EU countries based on the Global Gender Gap Index and its four subindexes (Economic Participation and Opportunity, Educational Attainment, Health and Survival, Political Empowerment)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Regarding economic autonomy, the findings of this study are consistent with the facts that women are rarely found in the top positions in the business world, their incomes are generally lower than men's, even in identical jobs, and they tend to face discrimination in the labor market [39]. Economic autonomy is a central pillar for women, and, by definition, it is necessary for them to earn income in order to overcome poverty and to be able to use their time freely to receive training, access the labor market, and achieve professional and personal development [40] (p. 182).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding economic autonomy, the findings of this study are consistent with the facts that women are rarely found in the top positions in the business world, their incomes are generally lower than men's, even in identical jobs, and they tend to face discrimination in the labor market [39]. Economic autonomy is a central pillar for women, and, by definition, it is necessary for them to earn income in order to overcome poverty and to be able to use their time freely to receive training, access the labor market, and achieve professional and personal development [40] (p. 182).…”
Section: Discussionsupporting
confidence: 87%